Analysis and Design of Mooring and Turret Systems for Ship-shaped Floating Production Systems (FPSOs) - Analyse og design av forankrings- og turretsystemer for flytende produksjonsskip (FPSO) - Svalastog, Åse Kristin Danbolt (NTNU, 2017)
From a marine operational point of view, a precise position and motion control of ships and other floating structures are important. In order to design a mooring system that can satisfy this, the top end motion of the mooring lines must be calculated. The excitation loads on a moored vessel are due to wind, waves and current. The wind is characterized as a static force excited by the mean wind speed, and as a low-frequency force excited by wind gusts. The waves are characterized by static mean forces, first order linear forces and second order non-linear wave forces. The current forces are considered as static forces. The main categories of station keeping are pure mooring systems, such as spread and single-point moorings, dynamic positioning systems and thruster-assisted mooring systems. Typical arrangements are taut, semi-taut and catenary systems. Mooring lines can be divided into several segments, with different material and buoyancy elements along the line. Mooring lines are often made of chain, synthetic fibre rope, wire rope or a combination of them. Three limit states are described; intact (ULS), accidental (ALS) and fatigue (FLS). Generally there are three different methods to compute the response of a floating structure; the frequency domain, time domain or a combined time and frequency domain approach. In the frequency domain, the non-linear restoring terms and damping terms are linearised and the low- and wave-frequency load effects are decoupled. The total contribution is then found by use of the superposition principle. In the time domain, the motions are solved simultaneously and non-linear effects are directly accounted for in the restoring and damping terms. The FPSO in question is located in the Barents Sea on the Norwegian Continental Shelf. The ship-shaped unit has a passive turret mooring system consisting of three bundles with five anchor lines each, resulting in 15 mooring lines. The vessel has in total 11 risers, with opportunity for future risers. A coupled SIMO-RIFLEX model provided by ...